2018
DOI: 10.5713/ajas.17.0629
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility and safety of KISS1 metastasis suppressor gene vaccine in immunocastration of ram lambs

Abstract: ObjectiveThe aim of this study was to investigate the reversibility and safety of KISS1 metastasis suppressor (KISS1) gene vaccine in immunocastration.MethodsSix eight-week old ram lambs were randomly divided into vaccinated and control groups. The vaccine (1 mg/ram lamb) was injected at weeks 0, 3, and 6 of the study. Blood samples were collected from the jugular vein before primary immunization and at weeks 2, 4, 6, 10, 14, 22, and 30 after primary immunization. All ram lambs were slaughtered at 38 weeks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Scrotal circumferences in oral and plasmid-injected vaccinated male goats were lower compared with those of the control groups from week 3 to week 14 after primary immunisation, and testes weight in oral and plasmidinjected vaccinated male goats was also lower compared with control groups, which indicated that immunisation of oral and plasmid-injected KISS1 DNA vaccines suppressed the testis growth of male goats. These results were similar with the immunisation effect of other KISS1 DNA vaccines in suppressing testis growth (Han et al, 2015(Han et al, , 2018a. Our results showed that the novel oral KISS1 DNA vaccine could achieve the same immunocastration effect as the plasmid-injected KISS1 DNA vaccine.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Scrotal circumferences in oral and plasmid-injected vaccinated male goats were lower compared with those of the control groups from week 3 to week 14 after primary immunisation, and testes weight in oral and plasmidinjected vaccinated male goats was also lower compared with control groups, which indicated that immunisation of oral and plasmid-injected KISS1 DNA vaccines suppressed the testis growth of male goats. These results were similar with the immunisation effect of other KISS1 DNA vaccines in suppressing testis growth (Han et al, 2015(Han et al, , 2018a. Our results showed that the novel oral KISS1 DNA vaccine could achieve the same immunocastration effect as the plasmid-injected KISS1 DNA vaccine.…”
Section: Discussionsupporting
confidence: 86%
“…KISS1 is a novel target for developing a DNA immunocastration vaccine. Our previous studies showed that immunisation against the plasmid recombinant KISS1 DNA vaccine (pVAX-HBsAg-S-KISS1-54-asd) can inhibit testosterone secretion, testis growth and sexual behaviour in ram lambs (Han et al, 2015(Han et al, , 2018a. To further improve the immunogenicity of the KISS1 DNA vaccine and reduce costs, we developed a novel oral KISS1 DNA vaccine containing tissue plasminogen activator (tPA) signal peptide and two copies of KISS1-54, which is presented by the attenuated Salmonella choleraesuis (C500) (Han et al, 2018b(Han et al, , 2019aDong et al, 2018).…”
mentioning
confidence: 99%
“…In this study, we established a model animal for immunization with the recombinant bacterium KISS1 gene vaccine (C500/pKS-asd) and investigated the immunocastrated effects of gene vaccine along with its effect on a cell-mediated immune response in immunized ram's testicular tissues using transcriptome analysis. The results of sexual behaviour evaluation, morphological and histological analysis of testis showed that C500/pKS-asd successfully inhibited testes growth, sexual behaviour and spermatogenesis through its effect on the release of hormones in the testes of the vaccinated group as observed in previous studies (Han et al, 2018;Wassie et al, 2019). Similarly, the results of hormone profile indicated that the concentrations of kisspeptin and testosterone in serum of vaccinated ram lambs were declined as compared to the control ram lambs, while anti-KISS1 antibody response in the vaccinated group was detected higher than that in the control group over the experiment period, which are alike with the finding of previous researches (Ramzan et al, 2015;Wassie et al, 2019).…”
Section: Identification Of Messenger Rna Expressions Related To Cellu...supporting
confidence: 79%
“…Recently, DNA vaccines have gained a considerable focus to control the fertility and reproductive efficiency in animals (Khan et al., 2008; Samoylov et al., 2019). The previous studies conducted in our laboratory demonstrated the effectiveness of KISS1 as a DNA immunocastration vaccine and showed the immune‐mediated neutralizing actions to reduce the function of gonads (Han et al., 2018; Han, Gu, et al., 2015; Wassie et al., 2019).…”
Section: Introductionmentioning
confidence: 93%
“…Immunocastration creates specific antibodies that recognize and bond to the hormone GnRH-I, preventing bonding with pituitary receptors, thus inhibiting FSH and LH secretion, causing infertility [10,12]. Thus, immunocastration has proven inhibition of reproductive activity in pigs [13][14][15], cattle [16,17], horses [18], sheep [19], mice [20][21][22][23], camelids [24], cats [25], chickens [26], and dogs [9,27,28]. Bansal and collaborators (2019) have recently developed and proven that immunogenicity of a vaccine able to develop immunity against GnRH and rabies virus simultaneously in mice [29].…”
Section: Introductionmentioning
confidence: 99%